An approach using fuzzy DEMATEL in identifiying the causes and effects of job stress among secondary school teachers / Siti Shakirah Shahpri - Shahpri, Siti Shakirah (2024)
Stress is defined as an individual's struggle to manage challenges from their surroundings, leading to feelings of unhappiness and lack of tranquillity. Job stress is a mental and physical state that influences one's productivity, effectiveness, and wellbeing at work. Individuals experiencing job stress may face negative emotional states and teachers are not exempt from encountering stress in the workplace. Therefore, this study aims to identify the causes and effects of stress among secondary school teachers using one of the multi-criteria decision-making (MCDM) method, fuzzy Decision Making Trial and Evaluation Laboratory (DEMATEL). Nine criteria were evaluated by collecting the data from three experts. The findings indicate that mental health, role conflict, and personal problems are the primary causes of stress. In contrast, job satisfaction, burnout, workload, student behaviour, environmental discomfort, and unrelated tasks are identified as effects of stress. Further analysis reveals that mental health is the most influential criterion, while job satisfaction is the most important criterion. This study is useful for the teachers themselves, as a way to self-monitor their emotional states, as well as to the top management of school and the authorities to take a proactive measure in providing a warm and supportive environment.